Clinical, Immunological, and Virological Outcomes Among Youths With Perinatal HIV After Transition to Adult Units in Spain From 1997 to 2016. (1st February 2021) - Aguilera-Alonso, David; Sainz, Talía; Jimenez de Ory, Santiago; Bernardino, Ignacio; Díez, Cristina; Torres, Berta; Merino, Dolores; Iribarren, José A.; Portilla, Irene; Ríos, María José; Ibarra, Sofía; Sanz, José; et al.
Abstract : Background: Children living with HIV are reaching adulthood and transitioning to adult clinics. This study aimed to describe clinical and immunovirological status after transition in patients with perinatal HIV. Methods: Patients participating in the Spanish multicenter pediatric HIV cohort (CoRISpe) transferred to adult care (FARO cohort) from 1997 to 2016 were included. Clinical and immunovirological data were collected from 12 years old to the last follow-up moment after transition (up to December 2017). We used mixed-effect models to analyze changes in CD4 counts or viral suppression and multivariate analysis for risk factors for virological failure (VF) and immune status after transition. Transition years were classified into 5-year periods. Results: Three hundred thirty-two youths were included. The median age at transition was 18 years (interquartile range: 16.3–18.9) and 58.1% women. The median follow-up time after transition was 6.6 years (interquartile range: 4.6–9.8), and 11 patients (3.3%) died. The immunovirological status at transition improved over the last periods. Globally, VF decreased from 27.7% at transition to 14.4% at 3 years post-transition ( P < 0.001), but no changes were observed in the last 2 transition periods. There were no significant differences in CD4 over the transition period. Risk factors for VF after transition were female sex, being born abroad and VF at transition, and for lower CD4 after transition were Romani heritage, younger age at transition, lower CD4 nadir, and CD4 at transition. Conclusions: After transition, virological suppression improved in the early transition periods, and immunological status remained stable. Nevertheless, some patients had higher risk of worse outcomes. Identifying these patients may aid during transition. Abstract : Supplemental Digital Content is Available in the Text.